ELECTROMYOGRAPHIC EVALUATION OF MASTICATORY MUSCLES IN PATIENTS WITH UNILATERAL CROSSBITE AND LATERAL MANDIBULAR SHIFT - Smaglyuk, L.V.; Chukhray, N.L.; Leshchuk, S.Ey. (World of Medicine and Biology, 2022)
Electromyography of masticatory muscles is informative and modern method of diagnostics in dentistry and in orthodontics particularly. Unilateral crossbite is associated with asymmetric activity of masticatory muscles. Electromyography was conducted in 20 patients with unilateral posterior crossbite with right side (9 patients) and left side (11 patients) mandibular shift in the period of the permanent dentition. The result of electromyography was a graphical representation and a digital characteristic of the contractility of the temporomandibular muscles. It was revealed association between unilateral posterior crossbite, chewing cycle and deviation in electromyography activity. The reducing of the masseter activity on the cross bite side and increasing on the non-cross bite side have been demonstrated.
Keywords: electromyography; masticatory muscles; malocclusion